The Funeral Achievements of Henry V at Westminster Abbey : The Arms and Armour of Death. - Curry, Anne (Royal Armouries research series, 2022)
Ground-breaking new studies of Henry V's chapel, tomb and funeral service have new revelations and insights into the time.